1996
DOI: 10.1002/art.1780390114
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to return to work among persons unemployed due to arthritis and musculoskeletal disorders

Abstract: Objective. To identify barriers to return to work (RTW) among persons likely to be seen in a clinician's practice who are unemployed due to arthritis and musculoskeletal disorders.Methods. Two hundred eighteen persons unemployed due to arthritis and musculoskeletal disorders were interviewed at baseline and followed up for 1 year, at which time their work status was ascertained. Backward stepwise logistic regression was used to determine the association of baseline clinical, sociodemographic, and work-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
(20 reference statements)
0
25
0
Order By: Relevance
“…Straaton et al (37) No effect Return to work Reisine et al (41) Positive Work disability (32) No effect Return to work Caine et al (53) No effect Return to work New York Heart Association classification Angina class III or IV No evidence Engblom et al (49) No effect Return to work Mark et al (32) No effect Return to work Exercise test f Insufficient Sellier et al (33) No effect Return to work (continued) (31) No effect Return to work Mark et al (32) No effect Return to work Flexible work schedule Insufficient Earle et al (58) No effect Return to work Able to work fewer hours Insufficient Earle et al (58) No effect Return to work Allowed to change work tasks Insufficient Earle et al (58) No start of the study (inception cohort) are not always well defined and may change in the course of the follow-up study. On the basis of this finding, we decided to use one category (ie, IHD).…”
Section: Work Disabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Straaton et al (37) No effect Return to work Reisine et al (41) Positive Work disability (32) No effect Return to work Caine et al (53) No effect Return to work New York Heart Association classification Angina class III or IV No evidence Engblom et al (49) No effect Return to work Mark et al (32) No effect Return to work Exercise test f Insufficient Sellier et al (33) No effect Return to work (continued) (31) No effect Return to work Mark et al (32) No effect Return to work Flexible work schedule Insufficient Earle et al (58) No effect Return to work Able to work fewer hours Insufficient Earle et al (58) No effect Return to work Allowed to change work tasks Insufficient Earle et al (58) No start of the study (inception cohort) are not always well defined and may change in the course of the follow-up study. On the basis of this finding, we decided to use one category (ie, IHD).…”
Section: Work Disabilitymentioning
confidence: 99%
“…Some articles focused on return to work after a coronary artery bypass graft or a percutaneous transluminal coronary angioplasty (PTCA). In the best evidence synthesis, we considered using the categories "IHD with operation" and "IHD without operation", but we found that the diagnosis of the patients included at the (35) No effect Work disability Straaton et al (37) No effect Work disability Reisine et al (7/22) (25) No effect (Nashville/Jyväskylä) b Work disability Sokka et al (40) No effect Work disability Puolakka et al (24) No effect Work disability Straaton et al (37) Negative Return to work Albers et al (38) Negative (39) No effect Work disability Work disability Borg et al (43) No effect Work disability Work disability Puolakka et al (24) No effect (25) No effect (Nashville) b Work disability Chung et al (25) Positive ( (25) No effect (Nashville/Jyväskylä) b Work disability Ever/never methotrexate Weak (+) Chung et al (25) Positive (Jyväskylä) b Work disability Chung et al (25) No effect (Nashville) b…”
Section: Best Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the general population, the prevalence of paid employment is estimated to be 4 -28% lower in patients with longstanding RA, whereas the prevalence of (partial) disability pensions is 11-52% higher (1). Because only a small proportion of patients that lost employment succeeded in regaining a paid job, the prevention of work loss from the earliest phase of inflammatory joint conditions onward seems crucial (6).…”
Section: Introductionmentioning
confidence: 99%